2020
DOI: 10.1177/0193945920967674
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Risk Factors for Lactation Mastitis: A Meta-analysis

Abstract: This meta-analysis was conducted to identify maternal risk factors for lactational mastitis. Studies published in English or Chinese were retrieved from Medline (PubMed), Embase, Cochrane Library, Web of Science, CNKI, WANFANG, and VIP databases according to predefined inclusion and exclusion criteria. Study quality was assessed by the Newcastle–Ottawa Scale. A random-effects model was used for data pooling and I2 tests to assess study heterogeneity. Pooled data from 8 cohorts and 10 case–control studies ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
(105 reference statements)
0
9
0
Order By: Relevance
“…Factors associated with ICLB were extracted from the resulting prior research; a 2020 narrative synthesis on risk factors for lactational mastitis ( Wilson, Woodd & Benova, 2020 ), a case-control study examining the risks for lactational mastitis ( Yin et al, 2020 ) and a meta-analysis of maternal risk factors for lactational mastitis ( Deng et al, 2021 ) (EH). These factors were cross-matched with the factors in the existing, ‘Breastfeeding Pain Reasoning Model’.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors associated with ICLB were extracted from the resulting prior research; a 2020 narrative synthesis on risk factors for lactational mastitis ( Wilson, Woodd & Benova, 2020 ), a case-control study examining the risks for lactational mastitis ( Yin et al, 2020 ) and a meta-analysis of maternal risk factors for lactational mastitis ( Deng et al, 2021 ) (EH). These factors were cross-matched with the factors in the existing, ‘Breastfeeding Pain Reasoning Model’.…”
Section: Methodsmentioning
confidence: 99%
“…A recent large case control study ( n = 652 participants) ( Yin et al, 2020 ), not included in the systematic review, investigated the association of 10 additional factors with lactational mastitis. Further, a meta-analysis on maternal risk factors for lactational mastitis ( Deng et al, 2021 ), found 13 significant factors, however methodological issues, such as those raised previously ( Senn, 2009 ), may have confounded findings. The overall high number of associated factors and inconsistencies across the studies can be confusing for clinicians to determine the potential influencing or contributing factors that form the foundation for the development of an appropriate individualised management plan.…”
Section: Introductionmentioning
confidence: 97%
“…Another report, by Mediano and coworkers (20), also noted that the use of a breast pump was associated with mastitis, however, the authors went on to suggest that this may be a consequence rather than a cause. Indeed, it was also noted that those studies that had observed a relationship between breast pump usage and the incidence of mastitis used retrospective data pooling, thus making it unclear if breast pump usage was a cause or a consequence of mastitis (21). In this connection, it was suggested that expressing milk by hand or by pump actually reduced the risk of mastitis and was therefore a useful technique for the prevention of mastitis during episodes of oversupply (22).…”
Section: Breast Pump and Breast Milk Expressionmentioning
confidence: 99%
“…In addition, lactation mastitis can be caused by the overproduction or irregular removal of milk from the breast [ 10 ]. Significant risk factors for lactation mastitis that have been recognized are previous mastitis during breastfeeding, breast trauma, latch problems ≤8 weeks post-delivery, milk overproduction, blocked duct, cracked nipple, use of nipple shields, breast pumps, and other factors [ 11 ]. The incidence of mastitis among breastfeeding women ranges between 10% (e.g., in the USA) [ 12 ] and 24% (e.g., in Australia) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%